2006
DOI: 10.2307/3844743
|View full text |Cite
|
Sign up to set email alerts
|

Predation Risk as a Driving Force for Sexual Segregation: A Cross-Population Comparison

Abstract: Sexual segregation is widespread throughout the animal kingdom. Although a number of hypotheses have been proposed to account for observed patterns, the generality of the mechanisms remains debated. One possible reason for this is the focus on segregation patterns in large mammals such as ungulates, where the majority of studies are descriptions of a single population. Here, we present the results of a cross‐population comparison of patterns of sexual segregation in the Trinidadian guppy, Poecilia reticulata. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 0 publications
1
82
0
Order By: Relevance
“…Similarly, in Crotaphytus dickersonae males fled sooner and tended to use more the refuges than females, which probably indicates stronger predation pressure on males (Plasman et al 2007). Therefore, as predator risk is generally higher for males than females (Ellingson 1994;Croft et al 2006), the sexual differences in antipredator behavior of several species of reptiles, including G. albogularis, are in agreement with theoretical predictions (Caro 1995;Ruxton et al 2004). …”
Section: Structure and Function Of Tail Displayssupporting
confidence: 70%
“…Similarly, in Crotaphytus dickersonae males fled sooner and tended to use more the refuges than females, which probably indicates stronger predation pressure on males (Plasman et al 2007). Therefore, as predator risk is generally higher for males than females (Ellingson 1994;Croft et al 2006), the sexual differences in antipredator behavior of several species of reptiles, including G. albogularis, are in agreement with theoretical predictions (Caro 1995;Ruxton et al 2004). …”
Section: Structure and Function Of Tail Displayssupporting
confidence: 70%
“…Here, we found that only large-bodied fish showed a significant preference for the size matched shoal, suggesting an increased importance of oddity for large fish compared to small ones. Large guppies are likely to be preferentially targeted by their predators [25], as they have a higher calorific value than small guppies, and major predators such as C. frenata are unlikely to be gape limited [35]. This, combined with their increased conspicuousness to visual predators, may make phenotypic matching highly important for large fish.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out this study at the University of the West Indies Biology Department laboratories in Tunapuna, Trinidad, using guppies from seven well known field sites in the rivers of the northern mountain range (table 2), representing a range of predation risks for the guppy [35], [46]. Guppies are sympatric with a variety of aquatic predators: the most significant of these is Crenicichla frenata which is large enough to consume even the largest guppies.…”
Section: Methodsmentioning
confidence: 99%
“…For the separate brain structures, we detected sexual dimorphism in both the olfactory bulbs and the cerebellum, which were larger in females (controlled for body size 2 and 14 %, respectively). Female guppies are generally much more active than males in terms of foraging activity, partially to compensate for costs associated with male harassment through increased foraging (Magurran and Seghers 1994;Croft et al 2006;Piyapong et al 2010). Females are also more innovative in a feeding situation, better at locating food and respond quicker to novel food sources (Laland and Reader 1999b;Laland and Reader 1999a).…”
Section: Intrinsic Sex Differences In Brain Morphologymentioning
confidence: 97%